2017
DOI: 10.3390/en10040502
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Biomass/Biochar Mixtures at Microwave Frequencies

Abstract: Material dielectric properties are important for understanding their response to microwaves. Carbonaceous materials are considered good microwave absorbers and can be mixed with dry biomasses, which are otherwise low-loss materials, to improve the heating efficiency of biomass feedstocks. In this study, dielectric properties of pulverized biomass and biochar mixtures are presented from 0.5 GHz to 20 GHz at room temperature. An open-ended coaxial-line dielectric probe and vector network analyzer were used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…That water shows lower conversion than the alcohol solvents can be ascribed to the fact that it has, even under hydrothermal conditions, a more extensive hydrogen bond network, which in turn results in an anomalously high dielectric constant; ~30 F m -1 at 250 °C [35]. A higher dielectric constant will reduce the capacity of the solvent to solubilise large organic molecules arising from the degradation of BSG which itself has an expected dielectric constant of ~2 F m -1 [36]. At elevated temperatures the dielectric constant of methanol is 6.02 F m -1 (240 °C), while those of ethanol and 2-propanol are 4.20 (240 °C) and 3.75 F m -1 (230 °C) respectively [37].…”
Section: Effect Of Alcohol Solvents On Solid and Organic Yield From Cmentioning
confidence: 99%
“…That water shows lower conversion than the alcohol solvents can be ascribed to the fact that it has, even under hydrothermal conditions, a more extensive hydrogen bond network, which in turn results in an anomalously high dielectric constant; ~30 F m -1 at 250 °C [35]. A higher dielectric constant will reduce the capacity of the solvent to solubilise large organic molecules arising from the degradation of BSG which itself has an expected dielectric constant of ~2 F m -1 [36]. At elevated temperatures the dielectric constant of methanol is 6.02 F m -1 (240 °C), while those of ethanol and 2-propanol are 4.20 (240 °C) and 3.75 F m -1 (230 °C) respectively [37].…”
Section: Effect Of Alcohol Solvents On Solid and Organic Yield From Cmentioning
confidence: 99%
“…wood sawdust) exhibit low dielectric properties limiting direct microwave-assisted thermolysis. 10,18 Previous work reported that the pine sawdust has a loss tangent (dT) of 0.01 which is ten times lower than water (dT ¼ 0.11) at 25 C and 2.45 GHz. 18 To overcome its low microwave absorbing properties, the biomass is generally mixed with microwave susceptors such as biochar, activated carbon or silicon carbide.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Since carbon materials are good microwave absorbers, biochar can be used to make more biochar by mixing it with biomass and submitting it to microwave heating. 16 Because of this property, activated biochar may be a sustainable and cost-beneficial alternative to graphene, and it may find use as electromagnetic shielding, microwave antenna, resonant sensor, and polymeric solar cell. 17,18 The activation process intends to improve the characteristics of regular carbon, such as electrical conductivity, sorption efficiency, and porosity.…”
Section: Introductionmentioning
confidence: 99%